2006
DOI: 10.1111/j.1442-2042.2006.01413.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycotic aneurysm of the renal transplant artery

Abstract: A case of mycotic aneurysm secondary to septicemia is reported. A 59-year-old man with end-stage renal failure underwent renal transplantation from a living donor. On the fifteenth postoperative day, he was febrile and his arm around an entry wound of the drip infusion had infectious signs. Cultures of the blood and pus discharge grew Methicillin-resistant Staphylococcus aureus . Vancomycin was administered intravenously for 30 days. Then the existence of a mycotic aneurysm on the transplant artery was not sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 11 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…Although rare, mycotic aneurysms have been known to complicate transplant surgery [16,17]. The incidence of mycotic aneurysms complicating liver transplantation is reported to be 0% to 3% [5,7,18].…”
Section: Discussionmentioning
confidence: 99%
“…Although rare, mycotic aneurysms have been known to complicate transplant surgery [16,17]. The incidence of mycotic aneurysms complicating liver transplantation is reported to be 0% to 3% [5,7,18].…”
Section: Discussionmentioning
confidence: 99%
“…So they are frequently seen at the anastomotic site and in the early weeks following surgery as a result of anastomotic defects. 3,6 Late presentation, as in this case after 14 years, is a very rare condition. In the literature, late spontaneous renal artery pseudoaneurysms seen at the anastomotic sites were reported between 15 months and 20 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical repair or transplant nephrectomy was most commonly used, Fujikata et al reported a case of conservative treatment for mycotic aneurysm without rupture. 4,6,9,10 In recent years, endovascular or percutaneous treatment of extrarenal pseudoaneurysms has been widely used. Although endovascular embolization is the most suitable technique in the treatment of intrarenal pseudoaneurysms and fistulas, there are limited endovascular techniques for treatment of the extrarenal pseudoaneurysms of transplanted kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Post-renal transplant patients often have multiple risk factors for opportunistic infections: intake of immunosuppressants, end-stage renal failure and diabetes mellitus in patients with diabetic nephropathy. Infectious pseudoaneurysms secondary to septicemia 5 or …”
Section: Discussionmentioning
confidence: 99%
“…5 Surgical plan should, therefore, be decided on an individual basis depending on the size of the pseudoaneurysm and on the microorganisms involved. Lifelong antibiotics were indicated, especially in those with immunosuppression, and regular surveillance follow-up is also required to rule out recurrence even after initial successful open repair.…”
mentioning
confidence: 99%